pH and microbial community determine the denitrifying activity in the presence of nitrate-containing radioactive waste - Mijnendonckx, Kristel; Bleyen, Nele; Van Gompel, Axel; Coninx, Ilse; Leys, Natalie (Frontiers in Microbiology, 2022)
Next to specific natural environments, certain industrial environments such as a geological repository for nuclear waste imposes highly alkaline conditions for thousands of years. Furthermore, some nuclear waste forms comprise nitrate concentrations, which necessitates the study of microbial nitrate reduction in highly alkaline conditions. Here, we compared nitrate reduction processes between two microbial communities at different pH related to a geological repository environment and in the presence of a nitrate-containing waste simulate during one year in batch experiments. We showed that the microbial community from the Boom Clay borehole was able to carry out nitrate reduction in the presence of acetate at pH 10.5, although the rates were much lower compared to at pH 9. However, microbial activity at pH 10.5 was likely limited by a phosphate shortage. Moreover, this study confirmed that the Harpur Hill sediment harbors a microbial community adapted to high pH conditions as it reduced twice as much nitrate at pH 10.5 compared to pH 9. Both communities were able to form biofilms on non-radioactive Eurobitum. However, for both microbial communities, pH 12.5 seems to be a boundary condition for microbial activity as no nitrate reduction nor biofilm was observed. Nevertheless, pH alone is not sufficient to eliminate microbial presence, but it can induce a significant shift in the microbial community and reduce its nitrate reducing activity. Furthermore, at the interface between the disposal gallery and the host rock, the pH will not be sufficiently high to inhibit microbial nitrate reduction.